The Refugee Health II Elective - Daniel Nicklas; Chelsea Wong; Jamaluddin Moloo; Paritosh Kaul (Association of American Medical Colleges, 2014)
Abstract Introduction While refugee health conditions are often amenable to primary care intervention and community support, asylum seekers and refugees are less likely to utilize health care and social services than other immigrant groups. Resettlement challenges, language barriers, stigma, and lack of knowledge of the health care system are just a few of the barriers to healthcare that refugees face. This clinical elective is geared toward fourth-year medical students interested in working with underserved populations and patients whose health is greatly affected by their unique cultures, personal histories, social circumstances, and legal circumstances. Methods At our home institution, this resource follows the Refugee Health Elective, which can also be found on MedEdPORTAL. This Refugee Health II Elective is designed to meet the curricular requirements of the ACGME with alignment between broad goals, specific learning objectives, educational activities, and evaluation. As learners experience this resource, they complete required reading assignments, community experiences at a refugee clinic where they are observed by a clinician, home visits, and a reflection paper. Results The Refugee Health II Elective has been well received at our home institution. Students have stated that: "The rotation and the opportunity to work with one of the most underprivileged populations in the Denver area very invaluable and fulfilling," and "I can't tell you how valuable it is to see the refugees outside of clinic and start to get a better sense of all of their challenges." Discussion Successful students have learned how to effectively use a translator, how to culturally negotiate clinical encounters, and how to incorporate the patient's unique life circumstance into their clinical encounters. They will be able to use these skills as they move forward in their medical careers.